Perlindungan Hukum Terhadap Penumpang Kereta Api Dengan Tiket Reduksi Dalam Hal Terjadi Kecelakaan Berdasarkan Undang-Undang Nomor 23 Tahun 2007 Tentang Perkeretaapian - Akmal Adyaksa; Anies Marsudiati Purbadiri; Na’imah; Sudjatmiko (Journal of Mandalika Literature, 2025)
Trains are one of the most popular modes of land transportation because they can accommodate many passengers in one trip, and the travel time is short because of their high speed. In Indonesia, train operations are managed by PT Kereta Api Indonesia (KAI) based on Law Number 23 of 2007 concerning Railways, including in terms of regulating the implementation of reduced tickets for certain groups, who are also entitled to legal protection when an accident occurs during the journey they are taking. The aim is to find out whether there is a difference in legal protection facilities between passengers with reduced tickets and normal tickets in the event of an accident during the journey. The research method is normative juridical, which means using railway laws and consumer protection laws as a means of review. The results of the study show that legal protection is provided equally even to passengers with reduced tickets, according to Article 132 paragraph (2) of the Railway Law, namely "Every passenger who has a ticket/ticket has the right to be transported by train". If during the transportation period an accident occurs due to train operations, PT KAI is responsible for replacing the losses suffered by passengers with a sum of money as compensation, the claim submission mechanism and amount of which are regulated according to the agreement between PT Asuransi Jasa Raharja and PT Jasaharja Putera with PT KAI and the Regulation of the Minister of Finance Number 37/PMK.010/008. Thus, it means that PT KAI has provided legal protection to its consumers without any discrimination.